Emerging biologic frontiers for Sjogren’s syndrome: Unveiling novel approaches with emphasis on extra glandular pathology - Li, Xiao Xiao; Maitiyaer, Maierhaba; Tan, Qing; Huang, Wen Hui; Liu, Yu; Liu, Zhi Ping; Wen, Yue Qiang; Zheng, Yu; Chen, Xing; Chen, Rui Lin; Tao, Yi; Yu, Shui Lian (Frontiers in Pharmacology, 2024)
Primary Sjögren’s Syndrome (pSS) is a complex autoimmune disorder characterized by exocrine gland dysfunction, leading to dry eyes and mouth. Despite growing interest in biologic therapies for pSS, FDA approval has proven challenging due to trial complications. This review addresses the absence of a molecular-target-based approach to biologic therapy development and highlights novel research on drug targets and clinical trials. A literature search identified potential pSS treatment targets and recent advances in molecular understanding. Overlooking extraglandular symptoms like fatigue and depression is a notable gap in trials. Emerging biologic agents targeting cytokines, signal pathways, and immune responses have proven efficacy. These novel therapies could complement existing methods for symptom alleviation. Improved grading systems accounting for extraglandular symptoms are needed. The future of pSS treatment may involve gene, stem-cell, and tissue-engineering therapies. This narrative review offers insights into advancing pSS management through innovative biologic interventions.